TRP channels and opsins: universal mediators of sensory biology and behavior - Montell, Craig (Henry Stewart Talks, 2025)
Sensory inputs and animal behavior, TRP channels, TRPV1 activation by painful heat and capsaicin, TRPγ required in proprioceptive neurons, Flies and humans respond to similar tastes, Infrared radiation (IR) as a new cue attracting mosquitoes